I SAID KUNGIL DOGIN … - Tajihon Tashboltaeva; Nigora Kholmatova (Galaxy International Interdisciplinary Research Journal, 2023)
One of the founders of this literary process, the "Malikush-shuaro" of his time, a talented poet and tazkiranavis Fazliy Namangani, will be looked at. An analysis of the poet’s ghazals is discussed.